(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Cross-sectional descriptive study on 369 pregnant women with a history of 2 or more prenatal check-ups who were delivered by medical staff at Thai Binh Obstetrics and Gynecology Hospital from January 1 to July 31, 2024. Method: Descriptive study through a cross-sectional survey on 369 pregnant women with a history of 2 or more cesarean sections who underwent cesarean sections at Thai Binh Obstetrics and Gynecology Hospital from January 1 to July 31, 2024. Results: The rate of pregnant women with a history of 2 cesarean sections was the highest at 78.6%. The rate of pregnant women who had emergency cesarean sections due to labor was 50.3%. The rate of scar adhesions was common in pregnant women at 44.1%. Pregnant women who had cesarean sections also had some complications. Conclusion: During surgery, patients with old scars are very susceptible to complications and surgery causes bladder damage in 1.1%, bowel damage in 0.23%. 33% of pregnant women require blood transfusion after surgery.